Efektivitas Pelayanan Via Online (PLAVON) Dukcapil - Siti Nafiatul Fikriyah; Hendra Sukmana (Univiversitas Dr. Djar Wattiheluw, 2023)
Public services aim to meet the needs of the community in carrying out rights and obligations and improving welfare that can realize a just and social order. In creating the effectiveness of public services in the government environment, a bureaucratic reform in public services is needed. The Indonesian government utilizes existing technology to create better public services by organizing online public services. The Sidoarjo Regency Government together with the Sidoarjo Regency Population and Civil Registration Office issued a new breakthrough in public services, especially in the service of population administration and civil registration with the issuance of the Via Online Service application (PLAVON). The purpose of this study was to determine and analyze the effectiveness of the Dukcapil Via Online Service (PLAVON) in Permisan Village, Jabon District, Sidoarjo Regency. This study uses qualitative research with a descriptive approach. The results showed of the effectiveness of the Dukcapil Via Online Service (PLAVON) in Permisan Village, Jabon District, was still not running optimally, especially in provision of socialization to the community.